Stable isotopes of carbon and nitrogen help to predict the belowground communities at a regional scale - Bing Wang (Nature Portfolio, 2017)
Abstract At the regional scale, although environmental factors are known to shape the distributions of belowground communities in terrestrial ecosystems, these environmental factors account for relatively low percentages of the variation in belowground communities. More of this variation might be explained by considering ecosystem stable isotopic values, which can provide insight into environmental conditions. Here, we investigated ecosystem (plant and soil) δ13C and δ15N values and belowground communities (microbes and nematodes) as well as environmental factors (climates, soils, and plants) across the Mongolian Plateau. The regression analyses showed that plant isotopic values were more closely associated with belowground communities than soil isotopic values, while ecosystem δ13C values were more closely associated with the belowground communities than ecosystem δ15N values. We also found isotopic values were more closely associated with nematode communities than microbial communities. Variation partioning analyses indicated that environmental variables together explained 16–45% of total variation in belowground communities. After isotopic variables were added as predictors to the variation partition analyses, the explanation of the variance was improved by14–24% for microbial communities and was improved by 23–44% for nematode communities. These findings indicate that isotopic values could be used to predict the properties of belowground communities at a regional scale.